Heuristic responses to pandemic uncertainty: Practicable communication strategies of "reasoned transparency" to aid public reception of changing science. (May 2023) - Hodson, Jaigris; Reid, Darren; Veletsianos, George; Houlden, Shandell; Thompson, Christiani
Scientific uncertainty during pandemic outbreaks poses a challenge for health communicators. Debates continue over the extent to which health officials should be transparent about uncertainty and the extent to which they should suppress uncertainty and risk losing the public's trust when information changes. The middle ground, the concept of "reasoned transparency, " proposes that communicators focus on interpreting uncertainty to the public in ways informed by risk research. However, little guidance exists for health officials on how to do so in this context. After conducting a series of one-to-one interviews about people's coronavirus disease 2019 information habits, we identified significant trends in the heuristics that people depended on to process uncertainty. Based on those trends, we propose health communicators use narratives of science as evolving to set expectations for change, and that when changes do occur, health communicators note divergences from the past and avoid simply replacing old information with new information.